Application of Blockchain Technology in e-LoA Technopreneurship Journal - Williams, Alexander; Dolan, Ellen (Aptisi Transactions On Technopreneurship (ATT), 2020)
LoA or Letter of Acceptance is a statement received. LoA is usually used as a statement of scholarship acceptance or even journal acceptance. In addition, the current issuance of LoA is still conventional, using paper as the access medium. This is certainly inefficient. In addition, the issuance of LoAs that can be accessed through the website also has certain problems. Many parties doubt the security of the LoA issued through the website, whether confidentiality is really maintained or not. To solve this problem, e-LoA (electronic LoA) was implemented using blockchain technology on the Technopreneurship Journal website. With the use of blockchain technology on this website, LoA data cannot be changed, duplicated or deleted. So that it can improve security and support transparency in the issuance and access of LoA. e-LoA issued through the website also makes it easier for parties to access and download a verified LoA.